Influence of psychoemotional stress on the functional activity of neutrophilic granulocytes and lipid peroxidation intensity in qualified athletes in competitive period - K. P. Bazarin; A. A. Savchenko (Acta Biomedica Scientifica)
The EEG can be used to obtain objective data on the level of situational anxiety in athletes. The dynamics of the psycho-emotional state of the athletes during the annual training-competitive macrocycle is characterized by the following features: in the preparatory and transition periods demonstrated by athletes level of anxiety and psycho-emotional stress is lower than in the control group. Competitive period is usually characterized by significant increase in anxiety. Competitive loads experienced by athletes on the background of low anxiety, lead to less pronounced decrease in functional activity of neutrophils and activity of the antioxidant defense system.